2009
DOI: 10.1002/ejlt.200900011
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Maillard reaction products

Abstract: Editorial 109 Editorial Antioxidant activity of Maillard reaction productsThe Maillard reaction is a non-enzymatic reaction in foods between reducing sugars and amino acids, peptides or proteins; it produces a complex array of compounds referred to as Maillard reaction products (MRP) [1]. The SCOPUS scientific database provides, as of 23 January 2009, a comprehensive list of 1821 articles dealing with MPR; some of them report on the antioxidant activity of MRP. The antioxidant activity of MRP has been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 14 publications
2
41
1
Order By: Relevance
“…They found that the AA (using the DPPH method) of Granny Smith apples dried at 60°C and 1.5 m/s in a convective drier increased by 87% after convective drying compared to raw apples. Other authors have also reported that processing either caused no change in the antioxidant activity of fruit and vegetables or enhanced it due to the improvement of antioxidant properties of naturally occurring compounds or formation of novel compounds such as Maillard reaction products with antioxidant activity (Amarowicz, 2009). Maillard-derived melanoidins, responsible for color change during the drying process, may be associated with increased antioxidant activity of the dried apples observed in the current study.…”
Section: Release Of Bioactive Compoundssupporting
confidence: 51%
“…They found that the AA (using the DPPH method) of Granny Smith apples dried at 60°C and 1.5 m/s in a convective drier increased by 87% after convective drying compared to raw apples. Other authors have also reported that processing either caused no change in the antioxidant activity of fruit and vegetables or enhanced it due to the improvement of antioxidant properties of naturally occurring compounds or formation of novel compounds such as Maillard reaction products with antioxidant activity (Amarowicz, 2009). Maillard-derived melanoidins, responsible for color change during the drying process, may be associated with increased antioxidant activity of the dried apples observed in the current study.…”
Section: Release Of Bioactive Compoundssupporting
confidence: 51%
“…The estimations of melanoidin, which are heterogeneous polymers of high molecular weight of brown color, have a very important role in discriminating the botanical origin of honey samples (Da Silva, Gauche, Gonzaga, Costa, & Fett, 2016). They are formed when sugars and amino acids combine (through the Maillard reaction) at high temperatures and low water activity (Amarowicz, 2009). In this way, the darkness of some honeys can be mainly attributed to the melanoidin which may indicate long periods of storage and/or honey heating processes (Borrelli, Visconti, Mennella, Anese, & Fogliano, 2002; Martins & Jongen, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the highest antioxidant activity of MRP-60 among the three MRPs, volatile compounds which were significantly correlated with antioxidant activity were listed in Table 2, according to the researches (Amarowicz 2009;Eiserich and Shibamoto 1994;Gomyo and Horikoshi 1976) and our previous study (Huang et al 2011). The content of pyrrole was 0.5763 μg/g in MRP-60 and 0.1354 μg/g in PXC, as reflecting the high positive correlations with antioxidant activity.…”
Section: Reducing Powermentioning
confidence: 97%